Efficacy of Drospirenone-Containing Hormone Replacement Therapy to Reduce Vasomotor Symptoms of Menopause - Dana A. Brown; Amy Henneman; Darshana N. Desai (MDPI AG, 2013)
Hormone replacement therapy has been proven efficacious for controlling vasomotor symptoms such as hot flushes associated with menopause. Drospirenone is a progestin with antiandrogenic and antimineralocorticoid activity that may be used in combination with estrogen to control hot flushes and offers the potential benefit of minimizing breast tenderness, blood pressure elevations and weight gain. Six clinical trials were reviewed. Of these, four trials explicitly listed hot flushes as a primary outcome. Efficacy with regards to hot flushes was found to range from modest to large (i.e., 37.5% to 94.6%), and four of the studies utilized diary cards to assess hot flushes. Results from these studies must be interpreted cautiously as quite a few limitations existed such as small population sizes involving specific ethnic groups, lack of p values with regards to baseline characteristics lending question to homogeneity, and inclusion of mostly healthy participants. Additionally, while the studies were long enough to see an effect, the long term effects of drospirenone-containing hormone replacement therapy (HRT) is unknown. The available data supports the use of drospirenone-containing HRT for the treatment of hot flushes associated with menopause.